To rise in darkness : revolution, repression, and memory in El Salvador, 1920-1932 - Gould, Jeffrey L. (Duke backfile, 2007)
An investigation of the January 1932 massacre of thousands of rural laborers in El Salvador and its long-term cultural and political consequences.